MACROANATOMIC CHARACTERISTICS OF THE THYMUS GLAND IN RATS IN EARLY POSTNATAL ONTOGENESIS (Conferencea, 2021)
The thymus gland in newborns and 6-day-old rat pups is located directly in the anterior mediastinum behind the sternum. It is flattened in the anteroposterior direction and is covered on all sides by a capsule, the upper edge of which is at the level of the upper third of the sternum handle, and the lower one, corresponding to the level of aortic discharge.